2016
DOI: 10.21521/mw.5559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the presence of Cacoxenus indagator Loew. parasite larvae in brood chambers on the emergence rate and size of red mason bees

Abstract: Cacoxenus indagator is one of cleptoparasites most frequently found in the nests of Osmia bicornis L. The goal of this experiment was to examine the influence of the presence of 2-3 C. indagator larvae in the brood chamber on the cocoon mass, on the mass and size of bee imagines, and on their emergence rate. During the analysis of red mason bee nest material, 200 cocoons were taken from brood chambers, each of them also containing 2-3 larvae of C. indagator (CC). The control group consisted of 200 randomly cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The same authors determined that in comparison with one-year-old tubes, in the two-yearold cane tubes there are more than ten times less healthy cocoons and three times more injured or destroyed cocoons, with a wider diversity of parasites [33]. Additionally, it was previously reported that continuous breeding in the same place for more than ten years means significantly higher numbers and diversity of brood parasites in nests [34,35]. Our results showed the lowest determined bees SL was at L3, which was 13.80% in total, while in a similar environment of L2, it was 28.05%.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors determined that in comparison with one-year-old tubes, in the two-yearold cane tubes there are more than ten times less healthy cocoons and three times more injured or destroyed cocoons, with a wider diversity of parasites [33]. Additionally, it was previously reported that continuous breeding in the same place for more than ten years means significantly higher numbers and diversity of brood parasites in nests [34,35]. Our results showed the lowest determined bees SL was at L3, which was 13.80% in total, while in a similar environment of L2, it was 28.05%.…”
Section: Discussionmentioning
confidence: 99%